Developing a post-operative pain assessment instrument and the effect of introducing pain assessment with activity (deep breathing and walking) as part of the post-operative monitoring on reducing post-operative pain severity - Dofitas, Rodney B.
Background: The past decade has seen increased knowledge in the provision of postoperative pain relief. This has been the result of a better understanding of the neurophysiological basis of pain relief, improved methods of organization and delivery of analgesic techniques, and changes in surgical practice. However, despite these improvements, numerous investigators still recognize the widespread inadequacy f postoperative pain relief. Many factors contribute to the widespread inadequacy of acute pain relief. This includes the perceived difficulty in assessing pain, inadequate patient empowerment, limited health professional education on the proper management of pain, negative connotations associated with opioid analgesics. This study describes a common sense approach to pain management which is simple and safe and which could be valuable in a developing counbtry like ours where resources are very limited. The effectiveness of introducing a policy on assessing portoperative pain during activity (deep breathing, coughing, and walking) in reducing the severity of postoperative pain and its interference on deep breathing, coughing and walking ability has not yet been investigated in our country. Sofar, no pain assessment instrument has been validated and routinely used for assessment of postoperative of pain and pain interference with deep breathing, coughing and walking. Interference with deep breathing, coughing and walking is a better way from a clinical perspective than pain intensity alone. For after all, it is the interference by pain, to these key physical activities that are known to be major determinants to the development of respiratory and cardiac complications. These two are the most common causes of postoperative mortality.